Emergency Remote Teaching and Learning and Teachers' Digital Competence - Filipa Seabra; Luísa Aires; Marta Abelha; António Teixeira (Universidad Autónoma de Baja California, 2023)
The challenges posed by the COVID-19 pandemic forced schools to quickly mobilize toward emergency remote teaching and learning (ERTL) practices. Teachers' digital competences were essential in this context. This study aims to identify the ERTL practices adopted in Portugal and how they were perceived by teachers of students aged 3 to 18. Data were gathered through a questionnaire administered online during April and May 2020 to 329 teachers. ERTL was perceived as an opportunity to develop their own and their students' digital competences. Teachers expressed a moderately positive view of the process and reported an experience of work overload. The pedagogical practices implemented by teachers during this period were diverse and differed according to gender, self-assessment of digital competence, and level of education taught. Results point to the importance of continued teacher training to achieve quality distance education.